FETAL MACERATION IN A KANNI BITCH - S. Prakash; V. Prabaharan; S. Satheshkumar (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A pluriparous Kanni bitch which was presented with the history of brownish vaginal discharge. Detailed gynaecological examination revealed presence of macerated fetal bones in the birth canal. Further, ultrasonographic examination revealed fetal bones in the uterus. Treatment with dextrose and oxytocin successfully expelled the macerated fetus. Animal had an uneventful recovery with antibiotic coverage.